PENGENDALIAN SETIAP REKENING TERHADAP EFEKTIVITAS ARUS KAS PT. ABC - Sembiring, Indriana (LPPM Universitas Terbuka, 2018)
This study research aims to analysis how the accounts receivable control to effectivity of cash flow PT. ABC. The analysis performed is: analyzing the management of receivables system in the control and manage of the accounts receivable of the company. Data obtained from the company in the Financial report data form of period July 2013-June 2014. The analysis in this study has used the descriptive analysis, trend analysis, cash conversion cycle analysis, and Financial ratio analysis. The results of this research study indicate that PT. ABC implements a management, processing to manage and control receivables system based on SOP (Standard Operating Procedures), but in the actual implementation there are having some things that are not in accordance with SOP. The factors involve the amount of receivables PT. ABC such as credit sales percentage, sales terms, customer type, and collection of the billing invoice. The account receivable takes more than 30 days (n>30),it means that the amount of receivables owned is not enough to be converted into cash, impact to pay account payables to suppliers. The credit policy would like to apply, expected to provide optimal benefits and able to accelerate the collectible receivables so that it can be converted into cash immediately, to be used as working capital and pay the account payables PT. ABC. Tujuan penelitian ini adalah menganalisis pengendalian piutang dagang terhadap efektifitas arus kas. Data diperoleh dari perusahaan berupa data laporan keuangan periode Juli 2013–Juni 2014. Analisis yang digunakan dalam penelitian ini adalah analisis deskriptif, trend, cash conversion cycle, dan analisis rasio keuangan. Hasil dari penelitian ini menunjukkan bahwa PT. ABC memberlakukan sistem proses manajemen pengelolaan dan pengendalian piutang berdasarkan POS (Prosedur Operasi Standar), namun dalam pelaksanaannya masih terdapat beberapa hal yang tidak sesuai dengan POS. Faktor-faktor yang memengaruhi besarnya jumlah piutang PT. ABC yakni persentase penjualan kredit, ketentuan penjualan, tipe pelanggan, dan usaha penagihan. Piutang tertagih membutuhkan waktu lebih dari 30 hari artinya bahwa jumlah piutang yang dimiliki belum cukup untuk dikonversi menjadi kas, sehingga hal ini juga berdampak kepada pelunasan hutang-hutang PT. ABC kepada supplier. Kebijakan kredit yang diterapkan diharapkan mampu memberikan keuntungan yang optimal dan mampu mempercepat piutang tertagih sehingga bisa segera dikonversi menjadi kas untuk digunakan sebagai modal kerja dan membayar hutang dagang PT. ABC.